Pemanfaatan Potensi Lingkungan Sekitar Sekolah sebagai Sumber Belajar IPA untuk Meningkatkan Hasil Belajar Siswa - Heti Purnamadewi (Multidisciplinary: Journal of Education an Learning, 2025)
This study aims to improve students’ learning outcomes through the utilization of the school’s surrounding environment as a learning resource in science education. The classroom action research was conducted at MTsN 2 Pangandaran involving ninth-grade students in the 2024/2025 academic year. The research was carried out in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through learning achievement tests, student activity observations, and documentation. The results showed a significant improvement in students’ science learning outcomes, from an average score of 70.25 in the first cycle to 83.60 in the second cycle, along with increased activeness and scientific attitudes. The use of the local environment as a natural laboratory made learning more contextual, meaningful, and relevant to students’ daily lives. The findings highlight that environment-based learning effectively enhances science learning quality and encourages teachers to design innovative lessons rooted in local wisdom and environmental sustainability values.